ANALYSIS OF THE INFLUENCE OF CONSUMPTION, INVESTMENT AND EXPORT ON INDONESIA'S ECONOMICS GROWTH IN THE PANDEMIC YEAR 2020-2021 - Haya, Aqilla Fadia; Nikensari, Sri Indah; Nurjanah, Siti (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The impact of the pandemic is also caused not only in the health sector, but also in the economic and social fields. The Indonesian economy at the beginning of the pandemic was surprised by growth that fell sharply, which was -5.32% in the second quarter of 2020. The negative economic growth was caused by a decline in economic growth factors, one of which can be seen through the expenditure approach. This study aims to analyze the effects of consumption, investment, and exports on Indonesia's economic growth during the pandemic. The method used is quantitative, with the help of statistical applications, E-Views 9, with panel data regression techniques in 34 provinces in Indonesia. The results of this study show that household consumption, Foreign Direct Investment, and exports have a positive and significant impact on economic growth. in Indonesia, while Domestic Investment has a negative and significant impact on economic growth in Indonesia. Simultaneously, the relationship between household consumption, FDI, DI, and exports can explain economic growth through an expenditure approach without including government spending and imports. The results of the Random Effect Model found that the greatest influence was obtained from FDI, exports, household consumption, and DI, respectively. This is due to the pandemic which has caused economic activity in the most likely expenditure to encourage production activities, which is foreign investment. Furthermore, exports have the second largest impact in contributing to economic growth during the pandemic.